Explaining the Gradual Decline and Probable End of History of France's Traditional Policy in Africa in this New Era of Globalization - (:unkn) unknown (My University, 2022)
This paper proposes to briefly explain why the gradual decline and probable end of historyof France’s traditional policy in Africa in this new era of globalization. The gradual declineof France’s traditional policy in Africa is simply understood as the progressive decadence, in the path towards the end of history of France’ s evolving neo-colonial policy—of meta-morphic French neo-colonialism, on the African continent and in its sub-Saharan bosom inparticular, passing from libertinage and coercive prescriber gendarme to “peacekeeper” andreserves; from collusion to the pronounced appearance of arm-wrestling and criticism; fromtacit legitimacy to pronounced fed up; switches to the progressive breakdown of privileges, monopolies and abusive dominations; and from the open sky to hypocrisy, taboo and sacrilege. By using Central African Republic and Mali as specific cases of concrete illustrations, the results that emerge from this paper show that the rise of soft engagement and the decline of hard engagement, the pronounced exposureof win-lose results of the said policy, the rise of new anti-neocolonial public opinion and the retreat of French power on the African continent and in its sub-Saharan bosom in particular are the main root causes of the gradual decline of France’s traditional policy in Africa and towards its probable end of history in this new era of globalization. To conclude, this paper has noted the need for further in-depth studies in the sense of identifying and seeing the results and implications of the decline of the said policy in this new era of globalization.
Keywords: African Research